Hal Higdon's smart running Expert advice on trainning, motivation, injury prevention, nutrition, and good health for runners of any age and ability - Higdon, Hal (Rodale Press ; Distributed in the book trade by St. Martin's Press, 1998)
Presents questions and answers from the "Ask the Experts" column on America Online, with tips on equipment, technique, training, racing, and health and fitness.